Neutrophil Elastase Inhibitors Suppress Oxidative Stress in Lung during Liver Transplantation. (23rd November 2019) - Yao, Weifeng; Han, Xue; Guan, Yu; Guan, Jianqiang; Wu, Shan; Chen, Chaojin; Li, Haobo; Hei, Ziqing
Abstract : Background . Neutrophil infiltration plays a critical role in the pathogenesis of acute lung injury following liver transplantation (LT). Neutrophil elastase is released from neutrophils during pulmonary polymorphonuclear neutrophil activation and sequestration. The aim of the study was to investigate whether the inhibition of neutrophil elastase could lead to the restoration of pulmonary function following LT. Methods . In in vivo experiments, lung tissue and bronchoalveolar lavage fluid (BALF) were collected at 2, 4, 8, and 24 h after rats were subjected to orthotopic autologous LT (OALT), and neutrophil infiltration was detected. Next, neutrophil elastase inhibitors, sivelestat sodium hydrate (exogenous) and serpin family B member 1 (SERPINB1) (endogenous), were administered to rats before OALT, and neutrophil infiltration, pulmonary oxidative stress, and barrier function were measured at 8 h after OALT. Results . Obvious neutrophil infiltration occurred from 2 h and peaked at 8 h in the lungs of rats after they were subjected to OALT, as evidenced by an increase in naphthol-positive cells, BALF neutrophil elastase activity, and lung myeloperoxidase activity. Treatment with neutrophil elastase inhibitors, either sivelestat sodium hydrate or SERPINB1, effectively reduced lung naphthol-positive cells and BALF inflammatory cell content, increased expression of lung HO-1 and tight junction proteins ZO-1 and occludin, and increased the activity of superoxide dismutase. Conclusion . Neutrophil elastase inhibitors, sivelestat sodium hydrate and SERPINB1, both reduced lung neutrophil infiltration and pulmonary oxidative stress and finally restored pulmonary barrier function.